Reduced circulating STOX1 is associated with inflammatory cytokines and insulin resistance in obese individuals: a cross-sectional study - Wang, Yanping; Xiang, Mingliang; Jiang, Xianmei; Shuai, Mingsha; Jian, Li; Geng, Shan (Frontiers in Nutrition, 2026)
IntroductionExcess adiposity drives adipose tissue dysfunction and metabolic disease, including type 2 diabetes and cardiovascular disorders. Building on our prior GEO-based analyses that nominated Storkhead box 1 (STOX1) as a candidate biomarker of obesity-related adipose inflammation, we compared circulating STOX1 between individuals with normal weight and those with overweight/obesity and examined its metabolic correlates.MethodsIn 476 volunteers, we quantified serum STOX1, adipokines, and clinical parameters; we further contrasted STOX1 and adiponectin between groups and performed an oral glucose tolerance test (OGTT) to assess glycemic effects on STOX1.ResultsSerum STOX1 was significantly lower in overweight/obese (OW/OB) participants than controls (controls: 1.27 ± 1.40 µg/L; OW/OB: 0.69 ± 0.77 µg/L; p < 0.001), accompanied by reduced adiponectin in OW/OB. Partial correlations showed inverse associations of STOX1 with metabolic and inflammatory indices and a positive association with adiponectin. In multivariable linear regression, systolic blood pressure (SBP), tumor necrosis factor-alpha (TNF-α), and body fat percentage independently predicted STOX1 (Y_STOX1 = 2.569 – 0.110 × SBP – 0.272 × TNF-α – 0.106 × body fat %; R = 0.37, R2 = 0.13).DiscussionDuring OGTT, hyperglycemia suppressed circulating STOX1, suggesting glucose-dependent regulation of its secretion/release. Collectively, these findings indicate that decreased serum STOX1 tracks adverse metabolic and inflammatory profiles in obesity and support its potential utility as a noninvasive biomarker of adipose tissue inflammation in overweight/obese individuals.